Labor Productivity in Southeast Asian Emerging Market Countries: The Role of Education and Digitalization (2000-2023) - Utama , M. Munip; Aji, Rizqon Halal Syah; Chalid, Pheni Chalid (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2023)
This study investigates the impact of investment in education and digitalization on labor productivity in four emerging market countries in Southeast Asia (Indonesia, Malaysia, the Philippines, and Thailand). The study uses dynamic panel data (2000-2023) and fixed effects models to examine the effects of education investment (proxied by average schooling attainment) and digitalization (proxied by internet penetration) on labor productivity (measured by GDP per employed person). The findings show that current labor productivity is strongly influenced by labor productivity in previous years. Education investment does not show a significant effect on overall labor productivity. However, Malaysia and the Philippines show that the percentage of internet users, which reflects digital literacy, significantly affects their workforce productivity. In contrast, the percentage of internet users in Indonesia and Thailand does not yet fully reflect digital literacy, which can significantly affect productivity. Further analysis shows that education investment and digitalization jointly significantly affect labor productivity in all countries studied.